Enhanced immune reaction resulting from co-vaccination of WT1 helper peptide assessed on PET-CT. Issue 39 (25th September 2020) - Nakata, Jun; Isohashi, Kayako; Morimoto, Soyoko; Itou, Ryota; Kamiya, Takashi; Matsuura, Ai; Nakajima, Hiroko; Fujiki, Fumihiro; Nishida, Sumiyuki; Hasii, Yoshiko; Hasegawa, Kana; Nakatsuka, Shinichi; et al.
Abstract : Abstract: It has become evident that positron emission tomography/computed tomography (PET-CT) using 2-deoxy-2-[F-18]fluoro-D-glucose (FDG) (FDG PET-CT) can detect anti-tumor immune response induced by various immunotherapies. To evaluate whether FDG PET-CT could detect anti-cancer immune response caused by cancer vaccine therapy, we performed a retrospective analysis of FDG PET-CT imaging of patients who were treated with Wilms Tumor 1 (WT1) vaccine therapy in Osaka University during July 2008 and June 2018. Increased FDG uptakes were detected in WT1-vaccinated skin and their draining lymph nodes during the repeated vaccination. While the FDG uptakes seemed to decrease with time after the cessation of WT1 peptide vaccinations, persistence of FDG uptakes for years in WT1-vaccinated skin were also observed in 2 cases who showed good clinical course. Moreover, the FDG uptakes of patients treated with the combination vaccine of WT1 specific cytotoxic T cell (CTL) and helper peptides were significantly stronger than of those treated with the WT1 CTL peptide alone. Since it is evident that the combination vaccine can induce a more robust anti-tumor immunity than can CTL peptide vaccine alone, the FDG uptakes in WT1-vaccinated skin might reflect the degree of immune response. These results suggest that PET-CT might be a good tool for prediction of anti-tumor immune response induced by WT1 vaccine therapy. Larger scale prospective studies therefore seem to be warranted.